2020
DOI: 10.1386/ajms_00021_1
|View full text |Cite
|
Sign up to set email alerts
|

Beyond normalization and equalization on Twitter: Politicians’ Twitter use during non-election times and influences of media attention

Abstract: Twitter has already become one of the most important social media platforms for political communication. Concerning the use of Twitter in politics, two possible developments have been at the core of the theoretical discussion – equalization and normalization. As normalization seems to be the case in most western countries about politicians’ Twitter use, it is yet unknown to what extent this debate can be applied to non-election times. The aim of our study is threefold. First, we address the debate of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Vaccari & Valeriani, 2015). For instance, Rauchfleisch and Metag (2016) focused on politicians' replies and found that parliamentarians received the greatest number of replies per actor, followed by local politicians, citizens, and journalists. Although there is this growing body of descriptive research about the configuration of politicians' social media networks (Keller, 2020), there is little knowledge of how elected politicians' online interactions have evolved over time.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccari & Valeriani, 2015). For instance, Rauchfleisch and Metag (2016) focused on politicians' replies and found that parliamentarians received the greatest number of replies per actor, followed by local politicians, citizens, and journalists. Although there is this growing body of descriptive research about the configuration of politicians' social media networks (Keller, 2020), there is little knowledge of how elected politicians' online interactions have evolved over time.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…These platforms offer them a channel for addressing specific target groups and for communicating about politics (Popa et al, 2020). In particular, Rauchfleisch and Metag (2016) point to Twitter as an important factor in the agenda‐setting process because many journalists source news on Twitter, thus acting as multiplicators for the content emitted by politicians.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As a consequence, politicians' influence is no longer estimated exclusively on the basis of their coverage in traditional media, but also on their popularity on social networks, where follower numbers, shares, retweets and likes are the measure of their success. Politicians' activity on social networks is also considered to be a driver for media attention (Rauchfleisch and Metag 2020;Graham et al 2016). Social media activity is therefore a priority for female politicians, particularly given that research has shown they receive less media attention (Miller and Peake 2013;Baitinger 2015;Tromble and Koole 2020) and more negative coverage (Armstrong and Gao 2011;Ross et al 2013;Larson 2001) than their male counterparts.…”
Section: Communicating For Influence and Visibilitymentioning
confidence: 99%
“…The paucity of research on digital technologies and the power distribution among political actors in direct democratic campaigns might be related to the fact that: first, defining the power structure among political actors is more complicated in direct democratic votes than in electoral contexts; and second, referendums and popular initiatives are, compared to elections, relatively rare events in most established democracies. However, even in Switzerland, where citizens are regularly asked to cast their vote on various issues and legislative projects, research on digital technologies and power distribution is limited to electoral competitions (Klinger, 2013), non-electoral periods (Rauchfleisch & Metag, 2020), or both (Rauchfleisch & Metag, 2016). By investigating the effects of digital technologies in the Swiss direct democratic context, this study hopes to add new insights to the equalizationnormalization debate as we draw on a large dataset over an 11-year timespan covering a broad range of direct democratic campaigns.…”
Section: Introductionmentioning
confidence: 99%